Co-infection of two eukaryotic pathogens within clam populations in Arcachon Bay - Itoïz, Sarah; Mouronvalle, Clara; Perennou, Morgan; Chailler, Elisa; Smits, Morgan; Derelle, Evelyne; Metz, Sebastian; Le Goïc, Nelly; Bidault, Adeline; de Montaudouin, Xavier; Arzul, Isabelle; Soudant, Philippe; et al. (Frontiers in Microbiology, 2024)
The parasitic species Perkinsus olseni (= atlanticus) (Perkinsea, Alveolata) infects a wide range of mollusc species and is responsible for mortality events and economic losses in the aquaculture industry and fisheries worldwide. Thus far, most studies conducted in this field have approached the problem from a "one parasite-one disease" perspective, notably with regards to commercially relevant clam species, while the impact of other Perkinsus species should also be considered as it could play a key role in the disease phenotype and dynamics. Co-infection of P. olseni and P. chesapeaki has already been sporadically described in Manila clam populations in Europe. Here, we describe for the first time the parasitic distribution of two Perkinsus species, P. olseni and P. chesapeaki, in individual clam organs and in five different locations across Arcachon bay (France), using simultaneous in situ detection by quantitative PCR (qPCR) duplex methodology. We show that P. olseni single-infection largely dominated prevalence (46 to 84 %) with high intensities of infection (7.2 to 8.5 log-nb of copies. g-1of wet tissue of Manila clam) depending on location, suggesting that infection is driven by the abiotic characteristics of stations and physiological states of the host. Conversely, single P. chesapeaki infections were observed in only two sampling stations, Ile aux Oiseaux and Gujan, with low prevalences 2% and 14%, respectively. Interestingly, the co-infection by both Perkinsus spp., ranging in prevalence from 12 to 34 %, was distributed across four stations of Arcachon bay, and was detected in one or two organs maximum. Within these co-infected organs, P. olseni largely dominated the global parasitic load. Hence, the co-infection dynamics between P. olseni and P. chesapeaki may rely on a facilitating role of P. olseni in developing a primary infection which in turn may help P. chesapeaki infect R. philippinarum as a reservoir for a preferred host. This ecological study demonstrates that the detection and quantification of both parasitic species, P. olseni and P. chesapeaki, is essential and timely in resolving cryptic infections and their consequences on individual hosts and clam populations.